Effects of Two Problem-Solving Instructional Strategies on Students’ Achievement and Science Process Skills in Biology Practical (2013)
The prevailing poor performance of students in biology is linked to their poor involvement in practical activities in biology as well as teachers‘ use of instructional strategies that do not promote acquisition of science process skills. Many earlier studies on problem solving instructional strategies aimed at addressing students‘ poor performance in biology did not involve the students‘ production of instructional materials needed for practical activities. In order to ascertain the effects of problem-solving instructional strategy on students‘ performance, it is useful to conduct a study that involves students using instructional materials they produced themselves. This study, therefore, determined the effects of two problem-solving instructional strategies (Bio Problem-Solving Instructional Strategy which involved the use of produced instructional materials and Gayford Problem-Solving Heuristics) on students‘ achievement and science process skills in biology practical. The study adopted a pretest-posttest control group experimental design with a 3 x 3 x 2 factorial design. The sample consisted of 828 students from nine randomly selected co-educational Senior Secondary Schools from three local government areas in Ibadan. Three schools each were assigned to two experimental and one control groups and the study lasted twelve weeks. The instruments used were: Achievement Test in Biology Practical (r=0.84), Science Process Skills Test (r=0.81), Mental Ability Test (r=0.86, Science Process Skills Assessment Inventory. In addition, Teachers‘ Guide on Problem Solving Instructional Strategy, Teachers‘ Guide on Modified Lecture Method and Guidelines for Evaluating Teachers‘ Performance were used for training teachers. Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using ANCOVA and Pairwise Comparison Post hoc test. There was significant main effect of treatment on students‘ achievement in biology practical (F(2,809) =14.8; p<.05). Students exposed to Bio Problem-solving Instructional Strategy ( =19.7) and Gayford Problem-Solving Heuristics (= 19.7) performed better than those in the Control group (= 17.9) in the Biology Practical achievement test. There was a significant main effect of treatment on science process skills in biology practical F(2,809)=182.4, p<.05. Students exposed to Bio Problem-Solving Instructional Strategy (= 42.8) performed better than those in Gayford Problem-Solving Heuristics (= 33.7) and control group (= 26.6) in science process skills test. Mental ability had significant main effect on students‘ science process skills (F(2,809)= 18.3; p<.05). Students of high mental ability (=37.0) performed better than the medium ability group (= 34.5) and low ability group (= 31.6). The interaction effects of treatment and mental ability on students‘ achievement (F4,809 =4.2; p<.05) and on science process skills, (F(4,809) =5.7; p<.05) were significant. Problem solving instructional strategies improved the performance of the students in biology practical with Bio Problem-Solving Instructional Strategy having more impact on students‘ science process skills in biology as well as providing greater transfer of learning to medium and low ability students. The use of materials produced by the students helped them to gain better understanding of the concepts taught and enhanced their level of acquisition of science process skills in biology. Therefore, teachers should employ problem solving instructional strategy in biology practical lessons.